Labour Democracy in 1952 - Gosselin, Emile (Relations industrielles / Industrial Relations, 1952)
SummaryIn the first section, the author comments briefly on the nature and the importance of the annual conventions of the Canadian labour bodies and on their political action. The reader will find in the second section a summary of the speeches, reports and resolutions presented during these conventions.